2022
DOI: 10.1002/acr.24625
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐Led Consultation for Patients With Rheumatoid Arthritis at Low Disease Activity: A Randomized Noninferiority Trial

Abstract: Objective To determine the effectiveness of nurse‐led consultations in patients with stable rheumatoid arthritis (RA) in Hong Kong. Methods The present work was a single‐center, randomized, open‐label, noninferiority trial. Patients who had rheumatoid arthritis (RA) with low disease activity (LDA) were randomized at a 1:1 ratio to attend a nurse‐led consultation or rheumatologist follow‐up visit for 2 years. The primary end point was the proportion of patients whose RA remained at LDA. Secondary end points inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…27 Also, the CQR19 has been used in different rheumatology settings when evaluating RA patients, as applied by rheumatologist, implemented in teleconsultation, and applied by nurses. [28][29][30] On the other hand, the properties of treatment regimen, such as adverse events, dose, frequency, and route of administration, also influence adherence. 21,22 In this study, patients treated with Golimumab, administered monthly, showed greater adherence at the end of follow-up, unlike those treated with weekly (Etanercept) and every 2 weeks (adalimumab) administration regimens.…”
Section: Discussionmentioning
confidence: 99%
“…27 Also, the CQR19 has been used in different rheumatology settings when evaluating RA patients, as applied by rheumatologist, implemented in teleconsultation, and applied by nurses. [28][29][30] On the other hand, the properties of treatment regimen, such as adverse events, dose, frequency, and route of administration, also influence adherence. 21,22 In this study, patients treated with Golimumab, administered monthly, showed greater adherence at the end of follow-up, unlike those treated with weekly (Etanercept) and every 2 weeks (adalimumab) administration regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals the age of 18 years or more and who met the 2010 ACR-EULAR classification criteria for rheumatoid arthritis [ 12 ] that defined as DAS28-CRP more than 5.1 for a 6-month or more period were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In China, rheumatology nursing service is not widely adopted because the feasibility and quality of rheumatology nursing service as part of a multidisciplinary team have not been confirmed in the Chinese population by the Chinese authorities. [12] The objectives of the retrospective study were to compare 2.5 years clinical outcomes of patients of rheumatoid arthritis with high disease activity (disease activity score 28-joint count with C-reactive protein (DAS28-CRP) more than 5.1) who received nurse-led care (nurse-supported care) against those of patients who received rheumatologist-led care for control of rheumatoid arthritis besides pharmacological treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that nurse‐led care is just as effective as rheumatologist‐led care for managing RA. This is based on randomised controlled trials (RCTs) comparing consultations provided by rheumatology nurse specialists to consultations provided by rheumatologists (Beauvais et al., 2022; Hoeper et al., 2021; Koksvik et al., 2013; Kwok et al., 2022; Larsson et al., 2014; Lopatina et al., 2021; Ndosi et al., 2014; Primdahl et al., 2014; Sørensen et al., 2015). The RCTs found that patients who received nurse‐led care were more satisfied with their care and had similar health outcomes as patients who received care from a rheumatologist (Bech et al., 2020; de Thurah et al., 2017; Garner et al., 2017; Sezgin and Bektas, 2021).…”
Section: Introductionmentioning
confidence: 99%